Early Infections and the Risk of Irritable Bowel Syndrome: A Case-Control Study. Issue 10 (November 2018) - Krajicek, Edward J.; Almazar, Ann E.; Larson, Joseph J.; Atkinson, Elizabeth J.; Talley, Nicholas J.; Saito, Yuri A.
Abstract : Goals: The goal of this study is to evaluate the association between early life infections and subsequent adult onset irritable bowel syndrome (IBS). Background: Infections during adulthood are a known risk factor for adult-onset IBS. This investigation examined the role of childhood infections and infection risk factors in the development of IBS symptoms. Study: In total, 1010 subjects (509 outpatients with IBS, 501 matched controls) were mailed questionnaires regarding early-life infections during infancy (0 to 12 mo), toddler years (1 to 3 y), and child years (4 to 18 y). Comparisons between cases and controls were performed using logistic regression adjusting for age, gender, and somatization score. Results: Around 648 (64.2%) subjects responded. The median age was 51.3 years (range, 18.0 to 70.7 y) and 535 (83%) were female. Childhood (below 18 y) infections were common in cases and controls (98% vs. 98%; P =0.465), with no differences between cases and controls during infant, toddler, and child-age periods. For gastrointestinal infections experienced below 18 years, no differences were observed by infection type (bacterial, viral, or parasitic) or age group. Cases were more likely to report bronchitis by age 18 [43% vs. 25%; P =0.003; odds ratio, 1.73 (1.20-2.51)], but not other common infections. Regular antibiotic exposure was greater amongst cases (43%) than controls (30%) [ P =0.09; odds ratio, 1.37 (0.96-1.96)]. The association between bronchitis and IBS case status remained significant after adjusting for antibiotic use ( P =0.01). Conclusions: Greater early childhood gastrointestinal infections rates were not observed in adult individuals with IBS compared with adult controls. The study does not support a statistically significant link between early life infections and IBS aside from bronchitis.